The Development of Interactive Learning Media Using Articulate Storyline 3 on the 'My Indonesia is Rich' Material for the Fifth Grade Students at SDN 07 Sitiung - Anggrayni, M; Susilawati, Wiwik Okta; Ramadani, Anggun Suci (The Future of Education Journal, 2025)
This research was motivated by the limited use of instructional media in the IPAS (Integrated Science and Social Studies) subject. The frequent use of conventional and monotonous media leads to student boredom, lack of engagement, and poor concentration, ultimately affecting learning outcomes. To overcome this problem, this study developed interactive learning media using Articulate Storyline 3 on the topic "Indonesiaku Kaya Raya" for fifth-grade students at SDN 07 Sitiung. The objective was to produce media that is valid, practical, and effective for elementary classroom use. This study employed a Research and Development (R&D) approach based on the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The analysis stage identified the needs of teachers and students and analyzed the subject matter. The design stage involved the development of teaching modules, media prototypes, and research instruments. During the development stage, the media underwent expert validation. The implementation stage tested the practicality and effectiveness of the media. Evaluation was conducted continuously throughout all stages. The validity test, conducted by nine experts, resulted in a score of 83.47% (very valid). The practicality test showed 75% teacher responses (practical), 86.28% student responses (very practical), and 90.75% module implementation (very practical). The effectiveness test reached 93.87%, indicating the media is very effective. Based on these results, the interactive learning media developed using Articulate Storyline 3 is considered valid, practical, and highly effective, and is therefore suitable for use in IPAS learning at the elementary school level.